Legal Systems Of The World : A Political, Social and Cultural Encyclopedia Volume I - IV - KRITZER, Herbert M (Editor) (Pentagon Press, 2005)
Legal Systems Of The World : A Political, Social and Cultural Encyclopedia Vol I-IV